Identifikasi Sebaran Akuifer di Desa Geneng, Kabupaten Ngawi, Provinsi Jawa Timur - Novianti, Yuniar; Saleh, Edward; Siswanto, Ari (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2025)
Ngawi Regency is one of the largest rice-producing regions in East Java. However, this area faces challenges related to water availability due to relatively low rainfall, making adequate groundwater sources essential to support agricultural irrigation systems. Therefore, analyzing subsurface geological characteristics is crucial for mapping the presence and distribution of aquifers as one of the primary sources of irrigation water. This research uses the Vertical Electrical Sounding (VES) method using the Schlumberger configuration to identify water-bearing rock layers. Data acquisition was conducted at six measurement points located in dry areas to minimize potential bias caused by soil moisture or surface water. These six points form a rectangular area, allowing the development of one-dimensional and three-dimensional subsurface models using IP2WIN and RockWorks software, with adjustments based on regional geological conditions. The interpretation results show that the research area consists of clay layers, silt layers, and sand layers which are included in alluvium deposits (Qa), where the sand layer is indicated as an aquifer. The aquifer depth ranges from 5.3 to 75 meters, with thicknesses varying between 7 to 33 meters at each measurement point. This aquifer layer is confined between low-porosity clay and silt layers, indicating that the aquifer is likely to be classified as a confined aquifer.